Analysis of Various Biblical Themes - Bissonnet, Peter (Scientific Research, 2018)
The author believes that people are turning away from Christianity because (due to their free will) they cannot believe in the validity of various concepts, such as a unique and universal Crucifixion. They believe that everything was localized to this insignificant planet and nowhere else, and, hence, Christianity is pretty blasé and probably has a lot of deceptions, misconceptions, etc., just like most of human history has. Of course, the Crucifixion occurred locally on this planet, but the implications for other planets in far off galaxies are just as crucial. Do earthlings make better Christians than those in some galaxy residing out where the quasars roam? No, we don’t. The Bible tells us to “prove all things”; in other words, reason analytically, responsibly, determine the truth! That is just what science does, or is supposed to do, but when scientists ally themselves too closely to government, their objectivity is capable of being bought or skewed by those governments, which keeps some subjects taboo as far as being investigated properly. This paper is trying desperately to determine what the truth is in those, admittedly strange events which have happened in the history of the New Testament. The author has also included a section on the search for new physical principles, by establishing working hypotheses and using these to analyze certain Bible miracles and such other phenomena which might seem appropriate. As a physicist and mathematician, the author finds the miracles of the Bible to be filled with a vast potential for discovery of new physical principles. The author hopes you will too.
Keywords: Unique and Universal Crucifixion; Synchronized Time Differentials/Intervals; Miracles; Search for New Physical Principles; Variable Gravitational “Constant”; Weak Interaction; Representations of Prime Numbers and Prime Products